Evaluation of Moving Image and Sound Archives Singapore (MISAS) database. - Lim, Irene Lei Lian. (2010)
The Internet has rapidly opened up new possibilities for infonnation providers such as archives to provide access to their collections. Many archives have gone online to provide easy access to their collections.